Studi Komparasi Alih Baring dengan Virgin Coconut Oil dan Olive Oil dalam Mengatasi Dekubitus Pasien ICU - Fitri Mahmudah; Sri Rahayu; Endar Sulistyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the implementation of repositioning combined with Virgin Coconut Oil (VCO) and olive oil in reducing early signs of pressure ulcers in patients in the ICU of Ir. Soekarno Sukoharjo Regional Hospital. The method used was a case study with a pre–post test approach. The results showed that all patients experienced improvement in skin condition, indicated by increased Braden Scale scores: patient 1 from 12 to 16, patient 2 from 10 to 13, patient 3 from 14 to 18, and patient 4 from 15 to 17. Patients treated with VCO showed faster improvement compared to olive oil, especially in improving skin moisture and reducing early signs of skin damage. In conclusion, repositioning combined with the application of VCO and olive oil was effective in reducing the risk of pressure ulcers in ICU patients, with an increase in Braden Scale scores of 3–4 points, where VCO showed more optimal results than olive oil. Keywords: Decubitus, ICU, Olive Oil, Position Change, Virgin Coconut Oil (VCO)